2023
DOI: 10.26668/businessreview/2023.v8i4.1216
|View full text |Cite
|
Sign up to set email alerts
|

Workplace Productivity Through Employee Sentiment Analysis Using Machine Learning

Abstract: Purpose: The objective of this study was to analyze workplace productivity through employee sentiment analysis using machine learning.   Theoretical framework: A lot of literature is already published on employee productivity and sentiment analysis as a tool, but the study here is intended to address the issues in employee productivity post-COVID’19.   Design/methodology/approach: The authors have studied the relationship between sentiments and workplace productivity post-COVID- 19. Sentiments were captured fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 2 publications
0
0
0
Order By: Relevance
“…The study population was composed of a sample of 863 researchers in the field of Machine Learning (also called Data Science or data mining according to context) encompasses a series of modeling techniques oriented to different organizational requirements (prediction of results, text analysis, artificial vision, voice recognition, etc. ), which can be applied to different tasks (Saxena et al, 2023) in business environments (Jordan and Mitchell, 2015;Alotaibi, 2023). In the education sector, the use of these techniques can be appreciated in tasks such as predicting the academic performance of students (Castrillón et al, 2020), while Salloum et al (2018) presented a text-mining approach to extract information from research articles.…”
Section: Methodsmentioning
confidence: 99%
“…The study population was composed of a sample of 863 researchers in the field of Machine Learning (also called Data Science or data mining according to context) encompasses a series of modeling techniques oriented to different organizational requirements (prediction of results, text analysis, artificial vision, voice recognition, etc. ), which can be applied to different tasks (Saxena et al, 2023) in business environments (Jordan and Mitchell, 2015;Alotaibi, 2023). In the education sector, the use of these techniques can be appreciated in tasks such as predicting the academic performance of students (Castrillón et al, 2020), while Salloum et al (2018) presented a text-mining approach to extract information from research articles.…”
Section: Methodsmentioning
confidence: 99%
“…They also found that various techniques are to be employed for multiple types of cancer. Saxena, Deogaonkar, Pais, and Pais (2023) the authors examined the connection between feelings and job efficiency following COVID-19. Seventy-two survey participants from a midsized consulting firm that participated in the study provided text inputs, and these sentiments were collected and correlated with the productivity scores.…”
Section: In Healthcare Strategic Managementmentioning
confidence: 99%
“…Duy Quang, 2023;Zhang Yanlong, Heli Wang, 2017). The institution is based on a view that emphasizes the dynamic interplay between organizations and institutions that defines the success of a company (Aguilera & Grøgaard, 2019;Saxena, S., Deogaonkar, A., Pais, R., & Pais, 2023). Cultural distance is an important component of mental distance, and it affects FDI inflows from nations (Contractor et al, 2020)).…”
Section: Introductionmentioning
confidence: 99%